Financial Reporting Quality on Dividend Payout Policy During Pandemic COVID-19 - Tessa Vanina Soetanto; Salzabila Musa; Thalia Angelica (Petra International Journal of Business Studies, 2024)
The COVID-19 pandemic disrupted the Indonesian business cycle and operations, leading to a stock market decline and reduced average dividend distribution as well as profitability, especially for manufacturing companies. This study investigates the pandemic’s influence on financial reporting quality in Indonesia and its relationship to dividend payout policy. We collected 455 observations from IDX-listed manufacturing companies (2016-2021) and processed them using descriptive statistics and logit regression with three models in Stata. Consistent with the outcome view, the logit regression results suggest that financial reporting quality is affected by the COVID-19 pandemic. Additionally, the three models unanimously display that financial reporting quality has a significant effect on dividend policy. RM1 shows a negative relationship, aligning with financial reporting quality’s impact on mitigating free cash flow problems. Contrarywise, the third model, RM2 identifies a positive and significant relationship consequent to enhancing the company’s image and shareholder satisfaction.